Adoption of opioid-prescribing guidelines in primary care: a realist synthesis of contextual factors. Issue 12 (30th December 2021) - Jacobson, Nora; Johnson, Roberta A; Schlabach, Christie; Incha, Jillian; Madden, Lynn; Almirall, Daniel; Hennessey Garza, Rose; Deyo, Bri; Schumacher, Nicholas; Stephenson, Christine; Quanbeck, Andrew
Abstract : Objective: As part of an effort to design an implementation strategy tailoring tool, our research group sought to understand what is known about how contextual factors and prescriber characteristics affect the adoption of guideline-concordant opioid-prescribing practices in primary care settings. Design: We conducted a realist synthesis of 71 articles. Results: We found that adoption is related to contextual factors at the individual, clinic, health system and environmental levels, which operate via intrapersonal, interpersonal, organisational and structural mechanisms. Conclusion: A single static model cannot capture the complexity of the relationships between contexts, mechanisms and outcomes. Instead, a deeper understanding requires a dynamic model that conceptualises clusters of contextual factors and mechanisms that tend towards guideline concordance and clusters that tend toward non-concordance. Trail registration number: ClinicalTrial.gov registration number NCT04044521 .